Imaging Gene Expression in Regional Brain Ischemia in Vivo with a Targeted [In]-Antisense Radiopharmaceutical - Toyofumi Suzuki; Yun Zhang; Yu-feng Zhang; Felix Schlachetzki; William M. Pardridge (Molecular Imaging, 2004)
The gene encoding glial fibrillary acidic protein (GFAP) is down-regulated 24 hr after reversible brain ischemia, such as with a middle cerebral artery occlusion (MCAO). The in vivo imaging of decreased GFAP gene expression in cerebral ischemia was examined in the present studies using a targeted peptide nucleic acid (PNA), which was labeled with 111 In, and which hybridized to nucleotides 20–37 of the rat GFAP mRNA. The PNA was monobiotinylated, and was attached to a monoclonal antibody (MAb) to the transferrin receptor (TfR) via a biotin–streptavidin linkage. The TfR MAb enables trans -membrane transport of the PNA antisense radiopharmaceutical from blood to the cytosol of brain cells. The decreased GFAP gene expression at 24 hr after a 1-hr reversible MCAO was confirmed by immunocytochemistry. The [ 111 In]-labeled PNA–MAb conjugate was administered intravenously to anesthetized rats at 24 hr after the 1-hr reversible MCAO, and the brain uptake of the targeted antisense imaging agent was decreased relative to brain regions outside of the infarct zone. These studies provide evidence that decreased expression of a target gene in brain can be imaged in vivo with a sequence-specific PNA, provided the antisense radiopharmaceutical is delivered across cell membranes with a receptor-specific targeting agent.